(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Our modern lifestyle provides us the luxury of using various products to make our lives more comfortable and easy, but it comes at a price. A common byproduct of our current lifestyle includes wastewater, which can either be in the form of water running down the shower or runoff from wet roads. This wastewater is unfit for human consumption or use.Fortunately, we can make the wastewater potable and usable by employing wastewater treatment technologies that filter and treat the wastewater by removing contaminants such as sewage and chemicals.Four common ways to treat wastewater include physical water treatment, biological water treatment, chemical treatment, and sludge treatment.